Pengaruh Internship Experience dan Learning Culture Terhadap Career Development Melalui Employee Adaptability Sebagai Variabel Intervening - Yudha Arya Finanda; Lutfi Nurcholis (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
Changing competency demands require Generation Z to develop adaptive career readiness. This study analyzes the influence of Internship Experience and Learning Culture on Career Development, with adaptability as a mediating variable. Grounded in experiential learning, learning organization, and work adaptation theories, this quantitative study uses Likert-scale questionnaires and is analyzed with SEM-PLS. The results show that both variables positively affect Career Development and enhance adaptability, which also mediates the relationship, highlighting the importance of practical experience and a supportive learning environment.